Effect of Cash Management on Profitability of Textile and Apparel Firms in Kenya - Kibogo Jemutai Janet; Kibet Lawrence K.; Kiplagat Nehemiah Kiprop (Kabarak University, 2025)
Abstract The textile and apparel industry in Kenya contribute significantly to the country’s export earnings. However, it faces profitability challenges due to increasing competition both locally and internationally. This study investigated the effect of cash management on the profitability of textile and apparel firms in Kenya. The study was anchored on the Miller-Orr Model. Employing a correlational research design, data was collected from all 75 finance managers across Nairobi, Machakos, Mombasa, Nakuru, Uasin Gishu, Kiambu, Kilifi, Kitui, and Kisumu using structured questionnaires. Given the small population, a census approach was applied. Data was collected using a structured questionnaire, achieving an 84% response rate (n=63). The findings revealed a strong positive and statistically significant relationship between cash management and profitability (r=0.817, p<0.05). Regression analysis further indicated that cash management accounts for 66.7% of the variance in profitability (R2=0.667). The regression coefficient (B=0.661, p<0.05) confirmed that a one-unit increase in cash management practices leads to a 0.661 unit increase in profitability. The findings support the rejection of the null hypothesis, confirming a significant positive effect of cash management on profitability. The study concludes that effective cash management is a crucial determinant of profitability in the Kenyan textile and apparel sector. It was recommended that firms prioritize the adoption of advanced cash flow forecasting models and maintain adequate liquidity reserves to enhance financial performance and ensure long-term sustainability.
Full text
Keywords: Cash Management; Profitability; Cash Forecasting; Liquidity Management.